Polyurethane/polyurethane nanoparticle‐modified expanded poly(tetrafluoroethylene) vascular patches promote endothelialization. Issue 8 (17th April 2018) - Zhang, Jun; Wang, Yutong; Liu, Cheng; Feng, Fuling; Wang, Dawei; Mo, Hong; Si, Ling; Wei, Guo; Shen, Jian
Abstract: Expanded poly(tetrafluoroethylene) (ePTFE) has been widely used as a vascular graft material due to the fact that it is durable, porous, flexible, and inert. However, ePTFE grafts easily induce thrombosis, calcification and neointimal hyperplasia in small‐diameter (<6 mm) graft bypass surgeries and thus cause surgical failure. Therefore, it is necessary to improve the in vitro and in vivo performances of ePTFE grafts. In this work, we first prepared a polyurethane/polyurethane nanoparticles (PU/PU‐NPs) composite film by a simple cosedimentation method. Compared with the pure PU film, the blood compatibility and the cell compatibility of the PU/PU‐NPs composite film were significantly improved. Then, we constructed a PU/PU‐NPs/ePTFE vascular patch (PPVP) by coating PU and PU‐NPs onto the surface of an ePTFE graft. PU‐NP modification endowed the ePTFE graft with the nanopatterned surface similar to the luminal surface of a blood vessel. PU NPs and the structural likeness of the surface synergistically optimized the overall performance, and thus improved the blood and cell compatibilities, effectively inhibited platelet adhesion, enhanced cell attachment and proliferation, and facilitated the formation of endothelial tissue—endothelialization. The abdominal artery patched with PPVP was not blocked and the endothelialization was achieved 30 days after the implantation. All the results taken together indicate that PPVP may be a promising alternative for a vascular patch. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2131‐2140, 2018.